Android-Based Learning Application Media for The Little One "SECIL" in Improving Communication of Children With Autism Spectrum - Pahrurrozi, Muhammad; Masitoh, Siti; Sujarwanto, Sujarwanto (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2023)
This study aims to determine the effectiveness of the use of the Little One's Learning Cereal Application (SECIL) media on the verbal communication skills of autistic children in Labschool Unesa inclusion elementary schools. This research is a single subject experimental research (Single Subject Research). The subjects in this study were several samples of autistic students in the inclusion elementary school Labschool Unesa. The design of this study was A-B-A'. Data collection using performance tests. The data analysis used is descriptive statistical analysis with analysis under conditions and between conditions. The results showed that the Little One's Learning Cereal (SECIL) media was effectively used in learning in improving communication skills for autistic students of Labschool Unesa Inclusion Elementary School. This is evidenced by the increase in communication skills scores before and after the intervention using the test, namely the average achievement score of 57.14% in baseline phase one to 79.76% in baseline phase two. In addition, the results of inter-condition analysis showed changes in stability from stable to stable, changes in data levels that increased, changes in direction and effects, and an overlapping percentage of data of 22.62%.